The Effect of Modernity, Economic Literacy, and Social Environment on Consumption Behavior of Senior High School Students - Aviani, Elma; Hardinto, Prih; Hardinto, Prih (Unversitas Negeri Malang, 2019)
The research aims at explaining the influence of modernity, economic literacy, and social environment on the consumption behavior of students. The study used a quantitative approach with the type of explanatory. The instruments in the research were questionnaires and written tests. The subjects of this study were 82 students. The results showed that (1) modernity had a significant positive effect on student consumption behavior; (2) economic literacy has a significant positive effect on student consumption behavior; (3) the social environment has a significant positive effect on student consumption behavior; (4) simultaneously, modernity, economic literacy, and social environment have a significant positive effect on student consumption behavior.